Cardiac Abnormalities in Type 1 Facioscapulohumeral Muscular Dystrophy. Issue 4 (June 2017) - Labombarda, Fabien; Maurice, Maxime; Simon, Jean-Philippe; Legallois, Damien; Guyant-Maréchal, Lucie; Bedat-Millet, Anne-Laure; Merle, Philippe; Saloux, Eric; Chapon, Françoise; Milliez, Paul
Abstract: Objectives: We conducted a retrospective study to characterize the cardiac complications in patients with genetically confirmed type 1 facioscapulohumeral dystrophy. Methods: We reviewed baseline cardiac investigations, including electrocardiogram, Holter electrocardiogram and echocardiogram, as well as cardiac complications that occurred during follow-up in 56 adult patients (37 men, mean duration of disease: 20 years). Results: Baseline evaluation revealed minor cardiac anomalies in 23 patients including incomplete right bundle branch block (iRBBB) in 13 patients (23%). Over a mean follow-up period of 7.2 years, there was no cardiac death, no patient developed cardiomyopathy, and 28 patients (50%) experienced cardiac anomalies. Among these patients, 3 had one or more major events (heart failure and/or atrial fibrillation). The remaining 25 patients presented minor cardiac anomalies of which iRBBB was the most frequent (25%). Conclusions: Cardiac anomalies identified during the follow-up of patients with type 1 facioscapulohumeral dystrophy are mainly minor anomalies, dominated by the iRBBB.